Heavy Metal Pollution in Aquatic Ecosystems: A Review of Toxic Impacts and Remediation Strategies - Abubakar, Musa Yahaya; Ahmad, Kabiru Bashir; Mathew, Twan Sale; Shamsudden, Ruslan; Muhammad, Haladu Mahmud; Haladu, Mohammed; Adam, Ansar Bilyaminu (Darul Yasin Al Sys, 2024)
Heavy metals contamination in aquatic ecosystems is a critical environmental issue with far-reaching implications for ecological health and human safety, Heavy metal pollution in aquatic ecosystems is a pressing environmental concern, posing significant risks to aquatic life and human health. This review summarizes the toxic effects of heavy metals (HMs) on aquatic organisms, ecosystems, and human consumers. The study explores the sources, fate, and transport of HMs in aquatic environments, highlighting their bioaccumulation, biomagnification, and ecological impacts. Remediation strategies, including phytoextraction, bioaugmentation, and chemical treatment, are critically eval_uated. Emerging technologies, such as Nano remediation and bioremediation, offer promising solutions. The study showed heavy metal pollution in aquatic ecosystems is a significant environmental challenge that requires coordinated efforts from governments, industries, and communities to mitigate its impacts and protect water quality and aquatic life. By addressing the sources and effects of heavy metals in aquatic habitats, we can mitigate their impact on the environment and human health, ensuring the sustainability of these vital ecosystems.